210Po in the marine biota of Korean coastal waters and the effective dose from seafood consumption. (August 2017) - Kim, S.H.; Hong, G.H.; Lee, H.M.; Cho, B.E.
Abstract: The activity concentrations of 210 Po were determined in plankton and selected species of macroalgae, crustaceans, molluscs, and fish from Korean coastal waters to understand 210 Po distribution in these trophic levels and to assess the effective dose of 210 Po from seafood ingested by the average Korean. The activity concentration of 210 Po in macroalgae, mixed plankton, anchovy (whole body), abalone muscle, and abalone viscera was 0.97–1.43, 32–137, 59–392, 2.93 ± 0.86, and 1495 ± 484 Bq kg −1 (w.w.), respectively. Polonium-210 concentration in the whole flesh of mussel and oyster were 47.8 ± 5.9 and 45.3 ± 7.1 Bq kg −1 (w.w.), respectively. Polonium-210 concentration in the muscle of the five tested species of fish other than anchovy ranged from 0.51 to 5.56 Bq kg −1 (w.w.), with the lowest amount in a demersal species. In fish, 210 Po activity concentration was as much as three orders of magnitude higher in viscera than in muscle. The average annual effective 210 Po dose per average Korean adult, who consumes 42.8 kg of seafood a year (excluding anchovy), was estimated to be 94 μSv y −1, with 42–71% of this attributed to shellfish. Further studies are required to assess the dose of 210 Po from anchovy owing to its high activity concentration and the manner in which anchovy is consumed. Highlights: 210 Po in fish was enriched more in viscera than in muscle. Biomagnification of 210 Po was evident along trophic levels from macroalgae to abalone. 210 Po concentration in the muscle of fish was the lowest in a demersal species. Further studies are required to assess the dose for 210 Po from anchovy.